2004
DOI: 10.1111/j.1471-0307.2004.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy protein supplementation on the quality of ripening Cheddar‐type cheese

Abstract: The impact of soy protein isolate on the proteolysis and organoleptic properties of Cheddar‐type cheese during ripening was studied. Cheese was prepared from cow's milk (control) and cow's milk plus soy protein isolate by using a starter culture of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus, and then ripened at 12 ± 1°C for 3 and 5 months. The molecular weight range and peptide fraction in the cheeses were determined by high‐performance liquid chromatography (HPLC), and the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…SE-HPLC was employed by Atia et al [79] to determine the mass distribution of the peptide fraction of Cheddar cheese elaborated from cow's milk enriched with a 5% of an SPI, with the aim of improving the organoleptic properties. Lioe et al [80] studied the presence of savoury peptides in moromi sauce obtained from the fermentation of yellow soybean.…”
Section: The Soybean Peptide Fractionmentioning
confidence: 99%
“…SE-HPLC was employed by Atia et al [79] to determine the mass distribution of the peptide fraction of Cheddar cheese elaborated from cow's milk enriched with a 5% of an SPI, with the aim of improving the organoleptic properties. Lioe et al [80] studied the presence of savoury peptides in moromi sauce obtained from the fermentation of yellow soybean.…”
Section: The Soybean Peptide Fractionmentioning
confidence: 99%
“…Rani & Verma (1995) reported that the color score increased with increase in proportion of soya milk in the cows milk increased. Atia et al (2004) reported that scores of texture and appearance were higher in control cheeses compared to cheeses with 5% to 7% soy protein isolate after 30 days. On the other hand, stretchability, appearance, and overall acceptability of pizza cheese samples increased but not significantly (p>0.05) as concentration of trisodium citrate increased.…”
Section: Resultsmentioning
confidence: 99%
“…Plant proteins, such as sesame protein, soy protein, and pea protein, have previously been incorporated into cheese matrices, in which changes to composition, sensory and textural properties, and microstructure were observed (Kumar et al 2011;Lu et al 2012;Ben-Harb et al 2018). Hsieh, Yun, and Rao (1993) showed that the addition of 2-3% soy protein to cheese milk resulted in Mozzarella cheese with a softer texture compared to the control, which could possibly be explained by the more open structure in cheese containing soy protein (Atia, Xia, and Zhang 2004). Similar findings have also been reported for low-fat Paneer cheese; Kumar et al (2011) investigated the effect of soy protein as a fat replacer, and reported that the firmness of low-fat Paneer cheese with soy protein addition was lower than that without soy protein.…”
Section: Incorporation Of Plant Proteins In Cheese Matricesmentioning
confidence: 99%